Spatial Temporal Analysis of Groundwater Fluoride Concentration and Its Implication to Human Health in Jakarta, Indonesia - Wacano, Dhandhun; Yoneda, Minoru; Yushananta, Prayudhy (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2025)
Groundwater serves as the primary source of potable water globally, including in Indonesia. Unfortunately, the presence of fluoride concentrations in groundwater, whether in ideal, insufficient, or excessive quantities, can have either beneficial or detrimental effects. Presently, the inhabitants of Jakarta persist in relying on groundwater as their primary source of clean water, which presents an escalating peril to public well-being as a result of increased domestic activities. Regarding the situation, this research aims to analyze the temporal trends and spatial distribution of fluoride concentration in groundwater and its potential consequences for public health risks in Jakarta. A total of 1,418 fluoride and temperature data from the Jakarta Environmental Agency was used for spatial-temporal analysis of 2016–2019 trends. We applied Microsoft Excel 2021 and ArcGIS Pro 3.2 for statistical and spatial data analysis. The result indicated that the fluoride concentration in groundwater was 72.14% below the minimum recommended value of 0.5 mg/L, mostly in the southern part of Jakarta. However, the average fluoride concentration for all seasons per year is consistently increasing, specifically in the northern part of Jakarta. Based on this research's findings, we concluded that the deficiency of fluoride concentration in groundwater is the majority problem in Southern Jakarta and could potentially cause dental caries if the groundwater is used as the daily source of clean water. This information is very useful for the government and public health authorities to further mitigate and protect people in Jakarta who still rely on groundwater as the source of clean water.